Pengembangan Media Geoquest Berbasis Artificial Intelligence untuk Pembelajaran Trigonometri Siswa Kelas XI SMAN 1 Percut Sei Tuan - Yulita Rotua Putri S. Sihite; Novitasari Br Hutauruk; Lutfiah Syahwarani Siregar; Esther Veronica Putri Siregar; Fevi Rahmawati Suwanto (Lembag, 2025)
This research aims to develop GeoQuest, an interactive learning media integrated with Artificial Intelligence (AI), to enhance the understanding of trigonometry concepts among Grade XI students at SMAN 1 Percut Sei Tuan. The development follows the Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The product integrates AI-based features such as adaptive practice questions, automated feedback, and dynamic visualizations of trigonometric graphs. Data were collected through expert validation, student response questionnaires, and learning outcome tests. The results show that the media meets the criteria of validity, practicality, and effectiveness. Material experts and media experts rated GeoQuest as